Monomers for adhesive polymers, 17.a Synthesis, photopolymerization and adhesive properties of polymerizable phosphonic acids bearing urea groups. Issue 1 (2nd January 2016) - Tauscher, Sven; Catel, Yohann; Moszner, Norbert
Abstract: Four polymerizable phosphonic acids bearing urea groups4a, 4b, 9a, and9b as well as the 10-(methacryloyloxy)decylphosphonic acid10 were synthesized in four to six steps. They were characterized by 1 H, 13 C, and 31 P NMR spectroscopy and by high-resolution mass spectroscopy. Contrary to methacrylates4a and4b, methacrylamides9a and9b were hydrolytically stable in deuterated water/deuterated ethanol solutions. The photopolymerization behavior of acidic monomers4a, 4b, 9a, 9b, and10 and their corresponding phosphonates were studied using a differential scanning calorimeter. Homopolymerizations and copolymerizations with N-butyl-N-ethylacrylamide were carried out. The presence of a urea group was found to significantly increase the rate of polymerization. Monomers bearing a phosphonic acid group were more reactive than their corresponding phosphonates. Self-etch adhesives based on monomers4a, 4b, 9a, and9b were able to provide a strong bond between a composite and the dental hard tissues (dentin and enamel). The presence of a urea group led to a significant increase in the shear bond strength to both dentin and enamel.